Evaluasi Penggunaan Antibiotik pada Pasien Sepsis di RSUD Ulin dengan Metode Gyssens dan ATC/DDD - Anugrahni, Chindy Monica; Aryzki, Saftia; Salwati, Salwati; Mustaqimah, Mustaqimah (SENTRI: Jurnal Riset Ilmiah, 2025)
Sepsis is a serious condition that occurs when the body overreacts to an infection, causing widespread inflammation and potentially threatening life. When an infection enters the bloodstream, it triggers a strong immune response that can disrupt organ function. This study aimed to examine antibiotic use in sepsis patients in the ICU of RSUD Ulin Banjarmasin in 2024. The analysis was conducted quantitatively using the ATC/DDD method and qualitatively with the Gyssens method. This retrospective observational study included a total of 14 patients, with data collected from June to July 2025. Results showed a total antibiotic use of 80.678 DDD/100, with Ceftriaxone being the most frequently used (52.2%) and Gentamicin the least (13.5%). The main antibiotics used were Ceftriaxone, Metronidazole, Meropenem 1 g, and Ceftazidime. Gyssens evaluation indicated that most antibiotic use fell into the appropriate category (category 0), while other combinations were in categories I to IVA. In conclusion, antibiotic use in the ICU exceeded WHO standards, which may risk resistance, but overall usage followed a rational and careful approach.